Some Fixed Point Theorems in Extended Cone \(b\)-Metric Spaces - Das, Abhishikta; Bag, T. (Communications in Mathematics and Applications, 2022)
In this paper, the notion of extended cone \(b\)-metric space is introduced, established the structure of the open ball and defined the notion of convergence of a sequence. Finally, restructured the Banach and Kannan contraction theorems without the normality condition in this new setting.